Odpowiedzi

2010-01-12T17:00:03+01:00
A) 3*(2x-1)+4(1-x)=6x-3+4-4x=2x-1

b) 2*(7x+5)-6(x-2)= 14x+10-6x+2=8x+12

c) -2x*(8-x)-5(x²+3x)= -16x+2x(kw)-5x(kw)-15x=-3x(kw)-21x

d) 5(3-2x)-(4x+6)*3= 15-10x-12x-18=-3-22x

kw - kwadrat
4 4 4
Najlepsza Odpowiedź!
2010-01-12T17:00:23+01:00
A) 3*(2x-1)+4(1-x)= 6x - 3 + 4 - 4x = 2x +1

b) 2*(7x+5)-6(x-2)= 14x + 10 -6x + 12 = 8x +22

c) -2x*(8-x)-5(x²+3x)= -16x + 4x² - 5x² - 15x = -x² - 31x

d) 5(3-2x)-(4x+6)*3= 15 - 10x - 12x -18 = -22x - 3
11 3 11
2010-01-12T17:12:59+01:00
A) 3*(2x-1)+4(1-x)=6x-3+4-4x=2x+1

b) 2*(7x+5)-6(x-2)=14x+10-6x+12=8x+22

c) -2x*(8-x)-5(x²+3x)=-16x+2x²-5x²-15x=-31x-3x²

d) 5(3-2x)-(4x+6)*3=15-10x-12x+18= 33-22x




4 4 4